미생물전기화학 혐기성소화조에서 전극간격이 메탄생성에 미치는 영향 - 신원범; 석붕; 조상열; 전항배 (한국수처리학회지, 25(4), 2017)
Electrode distance is a important factor for determining performance of bio-electrochemical anaerobic digestion (BEAD). In this study, the effects of electrode distances such as 0.3, 1.0, 3.0 cm on methane production, methane yield, organic matter removal efficiency, current density, coulombic efficiency, and energy efficiency were analyzed in a anaerobic digestor (AD) and BEAD reactors. COD removal efficiencies and daily methane productions in AD, BEAD(0.3), BEAD(1.0), and BEAD(3.0) reactors were 65.0, 75.8, 72.4, 68.1 % and 258, 357, 333, 276 mL/d, respectively. The current density and coulombic efficiency in BEAD reactor with electrode distance of 0.3 cm were 4.2 A/m2 and 62.6 %, respectively. As the electrode distance increased from 0.3 cm to 3.0 cm, COD removal and methane production from the BEAD reactor were decreased. From these results, the electrochemical performances (such as current density, coulombic efficiency, and energy efficiency) increased as the electrode distance decreased, on the same time the methane production and COD removal efficiency also increased from the BEAD reactor with narrower electrode distance. KCI Citation Count: 0